2017
DOI: 10.1080/10826084.2017.1356333
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Severity Among Adult Hispanic Immigrants: Examining the Roles of Family Cohesion, Social Support, and Gender

Abstract: Some potential clinical implications may be that strengthening family cohesion may enhance levels of social support, and in turn, lower alcohol use severity among adult Hispanic immigrants. Furthermore, strengthening family cohesion may be especially beneficial to men in efforts to lower levels of alcohol use severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
1
22
0
5
Order By: Relevance
“…Specifically, the effects of gender found in the present study support previous evidence that Latino males are more likely to engage in alcohol misuse compared to females [6]. In a study of recent Latino immigrants conducted by Cano and colleagues (2018), gender was found to moderate the association between family cohesion and alcohol use, with males having a higher alcohol use severity [48]. The results from the present study build on this evidence and support the notion that recent Latino immigrant males with a family history of substance use problems may be at particular risk for engaging in alcohol misuse post-immigration.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Specifically, the effects of gender found in the present study support previous evidence that Latino males are more likely to engage in alcohol misuse compared to females [6]. In a study of recent Latino immigrants conducted by Cano and colleagues (2018), gender was found to moderate the association between family cohesion and alcohol use, with males having a higher alcohol use severity [48]. The results from the present study build on this evidence and support the notion that recent Latino immigrant males with a family history of substance use problems may be at particular risk for engaging in alcohol misuse post-immigration.…”
Section: Discussionsupporting
confidence: 87%
“…Results from the present study add to this emerging literature to underscore the need to account for pre-immigration personal and family history of substance use when assessing Latino immigrants’ health risk behaviors, including alcohol use [15,28,47]. Previous research suggests that family history poses a significant influence on other family members, as parental drinking may affect the drinking motives of youth and resultantly influence their alcohol use patterns [48,49,50,51]. This association may be particularly relevant among Latino immigrants.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Explanations may include NDI artifacts related to nativity [41], less intensive marketing, or access to opioids among non-citizens. [2] Health affirming values placed on social mobility and family cohesion within traditional [42,43] or immigrant communities [44] may also mitigate economic stressors that contribute to depression and substance abuse. [42,43,44] Cultivating networks of support and resilience within communities affected by the opioid epidemic could help to prevent fatal overdoses in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the extent to which family conflict is associated with negative outcomes, particularly among children and adolescents, including poor emotional development (Amir, 2017; Borst, 2015), greater physical symptomatology (Chen, Brody, & Miller, 2017), psychological distress (Constantine & Flores, 2006), problem behaviors (Cummings, Koss, & Davies, 2015), obesity (Frontini, Canavarro, & Moreira, 2018), chronic pain (Voerman, et al, 2015), substance abuse (Cano, et al, 2018; Foxcroft & Lowe, 1995), anxiety disorders (Priest & Denton, 2012), post‐traumatic stress disorder (Norris & Uhl, 1993) (North & Pfefferbaum, 2013), and depression (Cummings, Koss, & Davies, 2015; Essau, 2004). In general, children and adolescents exposed to increased family conflict carry a disproportionate burden of chronic disease into adulthood and report poorer health status and quality of life (Borst, 2015; Chen, Brody, & Miller, 2017; Driscoll, et al, 2015; Repetti, Taylor, & Seeman, 2002; Shonkoff, Boyce, & McEwen, 2009).…”
Section: Family Conflict and Cohesionmentioning
confidence: 99%